The Influence of Price and Online Promotions on Guest Loyalty at Aston Batam Hotel and Residence - Haura sonia Listi; Rian Surenda (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of price and online promotion on guest loyalty at Aston Batam Hotel and Residence, addressing the growing competition in the hospitality industry where pricing strategies and digital marketing have become critical determinants of success. Using a quantitative research design with a causal associative approach, data were collected from 130 hotel guests selected through purposive sampling, employing structured questionnaires that were tested for validity and reliability. The data were analyzed using multiple linear regression with SPSS 25, supported by classical assumption tests. The findings reveal that both price and online promotion significantly and positively affect guest loyalty, both individually and simultaneously, with an adjusted R² value of 0.883. This indicates that 88.3% of the variation in guest loyalty is explained by the two variables, while the remainder is influenced by other factors. The study contributes to the hospitality marketing literature by highlighting the synergistic role of competitive pricing and consistent digital promotion in sustaining guest loyalty, and it provides practical implications for hotel managers to enhance customer retention in increasingly competitive markets